2018
DOI: 10.1149/2.0931805jes
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Electrolyte Oxidation and Film Deposition Characteristics at High Potentials in a Carbonate-Based Electrolyte Using Pt Electrode

Abstract: High voltage positive electrodes for lithium ion batteries have suffered from continuous oxidation of the electrolyte during cycling, which largely offsets the benefits of high energy and power densities. In this work, the electrolyte oxidation and concomitant film deposition/dissolution behaviors were investigated on Pt electrode by using linear sweep voltammetry (LSV), electrochemical quartz crystal microbalance (EQCM), and X-ray photoelectron spectroscopy (XPS). Two characteristics were identified. First, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Carbonate electrolytes also electrochemically oxidize at the cathode surface above 4.3 V and causes to release gases such as CO 2 and CO at the cathode side. [ 13 ] As a result, the evolved gases due to chemical and electrochemical oxidation of electrolytes at the cathode side cannot be decoupled easily. However, the evolution of O 2 is insignificant in the second and third cycles, and cannot enough to be detectable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbonate electrolytes also electrochemically oxidize at the cathode surface above 4.3 V and causes to release gases such as CO 2 and CO at the cathode side. [ 13 ] As a result, the evolved gases due to chemical and electrochemical oxidation of electrolytes at the cathode side cannot be decoupled easily. However, the evolution of O 2 is insignificant in the second and third cycles, and cannot enough to be detectable.…”
Section: Resultsmentioning
confidence: 99%
“…[ 6–9 ] It has been reported that the interfacial reactions upon charging of Li/NMC and graphite/NMC cells with carbonate electrolytes generate CO 2 , CO, H 2 and C 2 H 4 gases. [ 3,7,9–13 ] Nevertheless, the main source of hydrogen (H 2 ) gas at the early stage of solid–electrolyte‐interphase (SEI) formation is the reduction of residual trace H 2 O at the anode surface with the formula of H 2 O + e − → OH − + ½ H 2 . [ 7,8,14 ]…”
Section: Introductionmentioning
confidence: 99%
“…1a), which is also suggested for oxidation on Pt surfaces. 16 Electrolytes with fluorinated solvent molecules exhibits increased anodic stability. 7,8 This behavior is not inconsistent with our hypothesis, because CEI formed from fluorinated molecules should also be more stable against oxidation than CEI formed from standard organic battery electrolytes.…”
Section: G Further Discussionmentioning
confidence: 99%
“…Based on these computational and experimental findings, we adopt an alternative view of high voltage cathode interfacial reactions which has already been suggested for oxidation on Pt surfaces 16 (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation